IL-18 (Interleukin-18) Produced by Renal Tubular Epithelial Cells Promotes Renal Inflammation and Injury During Deoxycorticosterone/Salt-Induced Hypertension in Mice. Issue 5 (November 2021) - Thomas, Jordyn M.; Ling, Yeong H.; Huuskes, Brooke; Jelinic, Maria; Sharma, Prerna; Saini, Narbada; Ferens, Dorota M.; Diep, Henry; Krishnan, Shalini M.; Kemp-Harper, Barbara K.; O'Connor, Paul M.; Latz, Eicke; et al.
Abstract : IL-18 (interleukin-18) is elevated in hypertensive patients, but its contribution to high blood pressure and end-organ damage is unknown. We examined the role of IL-18 in the development of renal inflammation and injury in a mouse model of low-renin hypertension. Hypertension was induced in male C57BL6/J (WT) and IL-18 −/− mice by uninephrectomy, deoxycorticosterone acetate (2.4 mg/d, s.c.) and 0.9% drinking saline (1K/DOCA/salt). Normotensive controls received uninephrectomy and placebo (1K/placebo). Blood pressure was measured via tail cuff or radiotelemetry. After 21 days, kidneys were harvested for (immuno)histochemical, quantitative-PCR and flow cytometric analyses of fibrosis, inflammation, and immune cell infiltration. 1K/DOCA/salt-treated WT mice developed hypertension, renal fibrosis, upregulation of proinflammatory genes, and accumulation of CD3 + T cells in the kidneys. They also displayed increased expression of IL-18 on tubular epithelial cells. IL-18 −/− mice were profoundly protected from hypertension, renal fibrosis, and inflammation. Bone marrow transplantation between WT and IL-18 −/− mice revealed that IL-18-deficiency in non-bone marrow-derived cells alone afforded equivalent protection against hypertension and renal injury as global IL-18 deficiency. IL-18 receptor subunits—interleukin-18 receptor 1 and IL-18R accessory protein—were upregulated in kidneys of 1K/DOCA/salt-treated WT mice and localized to T cells and tubular epithelial cells. T cells from kidneys of 1K/DOCA/salt-treated mice produced interferon-γ upon ex vivo stimulation with IL-18, whereas those from 1K/placebo mice did not. In conclusion, IL-18 production by tubular epithelial cells contributes to elevated blood pressure, renal inflammation, and fibrosis in 1K/DOCA/salt-treated mice, highlighting it as a promising therapeutic target for hypertension and kidney disease. Abstract : Supplemental Digital Content is available in the text.